REGULASI PENINGKATAN NILAI TAMBAH NIKEL DAN PELUANG SERTA TANTANGAN BISNIS PERTAMBANGAN MINERAL DI INDONESIA - Sjahboeddin, Buana; Harjono, Dhaniswara Kwartantijono; Nainggolan, Bernard; Simatupang, Dian Puji (Indonesian Mining Journal, 2025)
This study provides a doctrinal examination of Indonesia’s legal framework regulating the increase of added value in nickel mining, with a particular focus on the coherence and enforceability of downstream mineral regulations. Employing a normative legal method combining statutory, conceptual, and analytical approaches, the research assesses the alignment between primary legislation—Law No. 4 of 2009 on Mineral and Coal Mining, as amended by Law No. 3 of 2020 and most recently by Law No. 2 of 2025—and its derivative instruments, including Government Regulation No. 23 of 2010 and successive ministerial regulations. Secondary legal materials, official government reports, international publications, and documented statistical data on nickel production and exports are examined to evaluate the extent to which the regulatory framework promotes domestic processing, legal certainty, and sustainable management of natural resources in accordance with the constitutional mandate of Article 33 of the 1945 Constitution. The findings indicate that regulatory interventions have substantively expanded domestic processing capacity and generated downstream investment, reaching approximately USD 5.03 billion, while increasing Indonesia’s nickel export value from USD 1.3 billion in 2021 to USD 6.8 billion in 2023. However, despite these economic outcomes, significant normative inconsistencies persist, including fragmented regulatory mandates, inadequate harmonization between central and sectoral regulations, and limited institutional capacity in licensing and supervision. These weaknesses manifest in ore–smelter imbalances, unequal distribution of benefits, and escalating environmental degradation, particularly deforestation, marine sedimentation, and heavy-metal contamination around mining areas. Such conditions reveal a structural discrepancy between the normative objectives of downstreaming and the principles of environmental protection, community rights, and sustainable governance mandated by Article 33 of the 1945 Constitution. This research contributes to the legal discourse by demonstrating that Indonesia’s nickel downstreaming framework remains predominantly instrumental and growth-oriented, lacking a coherent integration of environmental law, administrative accountability, and welfare-state obligations. Strengthening regulatory certainty requires harmonization of derivative regulations, binding environmental enforcement, and institutional safeguards to ensure equitable benefit distribution and long-term public welfare. These measures are crucial in operationalizing constitutional mandates and reinforcing the legitimacy of mineral governance in Indonesia.